Peran Learning Organization Dalam Meningkatkan Kinerja Dosen Di Universitas Bojonegoro - Maghfiroh, Inayatul; Amaliyah, Istiqfirul Hidayati; Fadhila, Leni Nur; Hendani, Hanna Putri; Anggraini, Lucia Dwi Rahma (Cendekia : Jurnal Pendidikan dan Keagamaan, 2025)
The aim of the research is to explore how Learning Organization can affect the performance of lecturers at Bojonegoro University. Learning Organization is a concept introduced by Peter Senge in "The Fifth Discipline", which emphasizes the importance of organizations continually learning and adapting to create the desired future. In the context of higher education, it is hoped that this concept can produce areas that support long-term education for lecturers. It is hoped that this will improve their performance in various fields such as teaching, research and community service. The research procedure applied is library research, which links the collection and analysis of literature related to the concept of Educational Organization and its implementation in a large learning context. Various literature sources such as books, journals, scientific articles, and research reports have been reviewed to gain an in-depth understanding of this topic. The research results show that the key elements of Learning Organizations, such as people development, systemic thinking, mental models, shared vision, and team education, have a significant role in improving lecturer performance. Lecturers who are active in the ongoing educational process tend to be more innovative, collaborative, and able to adapt to changes. In conclusion, the application of the Learning Organization concept at Bojonegoro University has great potential to improve lecturer performance and the overall quality of education. Based on these findings, the research also provides several practical suggestions for implementing Learning Organizations including improving professional development programs for lecturers, strengthening supporting infrastructure, and promoting a dynamic and collaborative learning culture in the university environment.